Effect of Working Capital Management Practices on Financial Performance of Hotels in Kenya: A Case of Selected Three Star Hotels in Garissa Town - Rashid , Aden Abdi; Butali, Peter; Odunga, Robert (International Journal of Finance, 2024)
Purpose: The main objective of this study was the effect of working capital management practices on the financial performance 3 star hotels in Garissa County. The study objectives was; to examine the influence of cash management practices, the effect of payables management practices, and effect of receivables management practices on financial performance 3 star hotels in Garissa town. Methodology: Three theories underpinned the study that is Theory of Working Capital Management, Cash Conversion Cycle Theory and Transaction Cost Theory. The research design used in the study was descriptive. The 171 employees of the chosen three-star hotels in Garissa Town were the target population where the sample of 120 participants was determined using Taro Yamane's formula (1967). Primary data were used in the study and was collected through a questionnaire through a drop-and-pick method. The Statistical Package for Social Sciences was used to analyze the data. Findings were presented using bar charts, graphs, and diagrams. Findings: The descriptive results revealed that all respondents were in agreement with statements on working capital management practices and its effect on financial performance. Additionally, the model summary results established that working capital management practices (cash management practices, payable management practices, and receivable management practices) accounts for 73.3% of variations in the financial performance of 3 star rated hotels in the county. The study further established that cash management practices, payable management practices, and receivable management practices bears a positive and significant effect on financial performance of hotels operating in Garissa Town as depicted by beta values of 0.593, 0.276 and 0.471 and significant values of 0.000, 0.004 and 0.000 respectively. The results imply that the financial performance of hotels operating in Garissa Town changes with respective beta values when each of the independent variable is increased with one unit. Unique Contribution to Theory, Practice and Policy: The study provided recommendations to the management of the hotels operating in Garissa Town to enhance working capital management practices such as cash management practices, payable management practices, and receivable management practices since the practices positively and significantly affects the levels of financial performance of the hotels."ƒ